Family physicians’ knowledge, beliefs, and practices in promoting healthy lifestyles and weight management for obese patients in Tabuk, Saudi Arabia - Alatawi, Amirah M.; Alanazi, Mansuor A.; Almohammadi, Maram Ati (Frontiers in Endocrinology, 2024)
Obesity is one of the most prevalent and relevant health problems in Saudi Arabia, and requires urgent attention. Family physicians are the first point of contact and one of the most important starting points for successful treatment of overweight and obesity. Aim: This study aimed to assess the knowledge, beliefs, and practices of primary care physicians in promoting healthy lifestyles and physical activity among obese patients. Methods: This cross-sectional study included family physicians who were board-certified or registered in a family medicine training program and working at government family health care centers in Tabuk. A predesigned structured questionnaire was distributed either in a written form or as an online survey. Results: The study included 83 family physicians. 84.1% only agree that overweight and obese patients should be screened for dyslipidemia, and only 67.5% agreed to offer advice on weight control even if the patient did not ask for it, demonstrating that Family Medicine physicians thought of physical inactivity (97.6%). Assessment of obesity counselling practices by Family Medicine physicians revealed that approximately three-fourths (75.9%) always calculated their body mass index(BMI) during obesity management, and comprehensive counselling on physical activity was higher (81.9%). The system for providing educational materials as part of managing overweight or obesity was inadequate, and 25.3% had never done so. Family medicine physicians had sufficient knowledge, positive beliefs about obesity management, and improper counselling practices. Lack of training and poor patient compliance with management plans are the main barriers to obesity control.